A digitized universal filtered orthogonal frequency division multiplexing for next generation communication applications. (November 2018) - Deepa, T.; Rama Rao, T.
Abstract: Universal filtered orthogonal frequency division multiplexing (UF-OFDM) is an alluring next generation 5G waveform for communication with small bursts transmission. Moreover, there are arising applications in which short data packet transmissions are awaited to carry fault-finding messages that must be obtained with low latency and high reliability. Visible light communication (VLC) acts as an ideal technology to accomplish these requirements. VLC uses intensity modulation and direct detection techniques and hence they require the signals to certainly be real valued positive sequences. In this paper, a digitized UF-OFDM based on delta sigma modulation (DSM) is proposed. The implementation of the proposed digital UF-OFDM is analyzed in comparison with continuous-time domain representation of UF-OFDM (CT-UF-OFDM). The simulation result exhibits that the system which is projected has better SNR performance than the digitized OFDM. It is found that around 15.8 dB of SNR is improved using the proposed scheme as compared to digital OFDM.